The Structure and the Duties of the Supreme Council of Health - Özdemir, Mehmet Hakan; Çekin, Necmi (The Bulletin of Legal Medicine, 1998)
The Supreme Council of Healt is a body under the Ministry of Health, composed for expertise in cases of medical malpractice and neglect. The structure, the relevant laws of the council and the legal procedures of its activities are presented and some difficulties in implications are discussed in this paper.Key words: Supreme Council of Health, Medical and legal responsibilty, Medical malpractice, Expertise.
Keywords: supreme council of health; medical and legal responsibility; medical malpractice; expertise